Effect of WWTP size on grey water footprint—Czech Republic case study - Libor Ansorge; Lada Stejskalová; Jiří Dlabal (Environmental Research Letters, 2020)
The number of wastewater treatment plants (WWTPs) in the Czech Republic is increasing. Wastewater, which was previously disposed of in other ways (e.g. septic tanks, cesspits etc), is now entering the surface water (after treatment at a WWTP). Billions of Czech crowns have been invested in the construction of new WWTPs or reconstruction and intensification of existing ones. This money had been invested to meet discharge standards for individual pollutants. However, the overall level of pollution associated with wastewater discharges has not been assessed. The indicator of grey water footprint was used to assess whether there was an increase in pollution load discharged from WWTPs between 2002 and 2018. Discharged pollution data from 4115 industrial and municipal WWTPs were analysed. The analysis of such a large data set has not been carried out yet and brings new knowledge concerning the effect of WWTP size on the grey water footprint. Overall, the total value of the grey water footprint (and thus of the discharged pollution level) decreased in the monitored period. Grey water footprint caused by the largest WWTPs decreased, while the grey water footprint of small WWTPs increased, due to the increase in their number. The decisive pollutants that determine the value of the grey water footprint are total phosphorus and ammonium nitrogen. Measures targeting these two main pollutants can significantly reduce the overall level of pollution load discharged from WWTPs.